PERANCANGAN JARINGAN SARAF TIRUAN HIERARCHICAL EXTENDED KOHONEN MAP UNTUK WAHANA GERAK MANDIRI PENGHINDAR TABRAKAN - INDRA HARTARTO TAMBUNAN (JURNAL ILMIAH MAKSITEK, 2018)
This paper describes a neural network Hierarchical Extended Kohonen Map design for an obstacle avoidance of autonomous vehicle. Hierarchical Extended Kohonen Map is developed from the principle of Extended Kohonen Map. A grid of competitive layer (sub-net) is added to every cluster of super-net competitive layer of Extended Kohonen Map. This neural network consists of 16 clusters of super-net competitive layer (4x4 neuron) and 10 clusters of sub-net competititve layer. The result shows that the proposed design of Hierarchical Extended Kohonen Map has responded well to vector input test